Social and Health Determinants of the Families of Children Under Two Years of Age with Stunting in Sigi District - Fahmi Hafid; Nasrul Nasrul; Adhyanti Adhyanti; Bohari Bohari (Poltekkes Kemenkes Palu, 2023)
Social aspect is a determinant of stunting. Stunting in children is an indicator of well-being and an accurate reflection of social inequality. This study aims to analyze the social and health determinants of the families of children under two years of age with stunting in Sigi District. This was an analytical study with cross sectional design which involved a population of children aged 6-23 months. A sample size consisted of 380 people were selected through cluster simple random sampling technique. Respondents involved the mothers of children under two years of age. Data collection was conducted in February-June 2022. The dependent variables was stunting incidence. The independent variables were maternal age, parity, birth spacing, maternal education, child's gender, child's age in months, length of birth, early initiation of breastfeeding, exclusive breastfeeding, breastfeeding status, child condition at the time of study, history of ARI, diarrhea, pulmonary tuberculosis, measles, Helminth Infection, utilization of health facilities, growth and development stimulation, complementary food, water sources, ownership of family latrines, food insecurity, housing, and smoking family members. Stunting data was obtained by measuring body length using the Length Measuring Board (LMB) and measuring age by reading the birth certificate or MCH book of the child. Other data were obtained by filling out the kobocollect questionnaire. Data were analyzed using SPSS version 22.00. The WHO-Antro 2005 software was applied to determine the Z-Score. Height-for-Age data were analyzed using univariate, bivariate and multivariate analysis using Backward logistic regression method. Ethical clearance was obtained from the ethics committee of Palu Health Polytechnic number 0011/KEPK-KPK/IV/2022. The results showed that children aged 12-24 months had a 4.1 times higher risk of experiencing stunting compared to children aged 0-6 months (AOR=4.1; 95% CI: 2.0-8.4). Furthermore, children aged 7-11 months had a 2.2 times higher risk of experiencing stunting compared to children aged 0-6 months (AOR=2.2;95%CI: 1.2-3.9). Children who had a length of birth of <48 cm had a 2.1 times higher risk of experiencing stunting compared to children who had a length of birth of ≥48 cm (AOR=2.1; 95% CI: 1.2-3.6). Children of women with education of <9 years had a 2.7 times higher risk of experiencing stunting compared to children of women with education of ≥9 years (AOR=2.7; 95% CI: 1.4-5.0). Children from families with food insecurity had a 1.6 times higher risk of experiencing stunting compared to children from families with no food insecurity (AOR=1.6; 95% CI: 0.9-2.7). Social and health determinants of children under two years of age with stunting in Sigi District were child's age, length of birth of <48 cm, maternal education and food insecurity.